Pemanfaatan Aplikasi Kahoot Dalam Pembelajaran Ipa Topik “Hewan Dan Jenis Makanannya” Kelas IV - Atika Nurohmah; Muhsinin (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2025)
This research aims to find out analyzing the development of learning media based on the Kahoot application on the material classification of animals based on the type of food in class IV Sdi which is valid. valid. This research applies the Research & Development research method research method with the 4-D model which consists of define, design, development and disseminate. Data collection techniques and data collection techniques and data analysis through interview techniques. Kahoot application development passed validation of media experts, linguists and material experts. Media expert validation results with a percentage of 95%, very good, linguists with a percentage value of 94% very good and material experts with a percentage of 92% very good so that the Kahoot application is very feasible to use as media in learning activities. application is very feasible to use as media in learning activities. Keyword: Validation, Application, Media and Learning